Two-dimensional optical coherence vibration tomography for low-frequency vibration measurement and response-only modal analysis. (15th October 2016) - Zhong, Jianfeng; Zhong, Shuncong; Zhang, Qiukun
Abstract: A high-speed camera-based two-dimensional optical coherence vibration tomography (2DOCVT) system with a subnanometre displacement resolution was developed and employed for low-frequency vibration measurement and modal analysis. Experimental results demonstrated the ability of low-frequency absolute displacement measurement of structural line vibrations without scanning. Three-dimensional (3D) surface displacement of a vibrating structure could also be obtained using the developed 2DOCVT by scanning the structure. The scanning 2DOCVT system acted like a 3D optical coherence vibration tomography system. The developed 2DOCVT system could capture structural modal parameters without vibration excitation input information, and therefore, it is a response-only method. The 2DOCVT could be recommended in the application of low-frequency vibration measurement and modal analysis of beam and plate structures, especially when the vibration amplitude is at nanometre or micrometre scale. Highlights: A subnanometre-resolution 2DOCVT system was developed for low-frequency vibration measurement and modal analysis. Three-dimensional displacement of vibrating structures could be obtained using the 2DOCVT by scanning the structures. The 2DOCVT is a response-only method that could capture structural modal parameters without input information.